Assessing the Viability of Algal Biodiesel as a Supplement to Liquid Fossil Fuels - Marvin Ashaba Aheebwa (Uganda Christian University, 2025)
The global energy and pollution scenario call for new sources besides fossil fuels as the source of a renewable energy input, particularly for developing economies like Uganda that are faced with energy insecurity, open economies, and environmental degradation due to the utilization of fossil fuels. Sustainability of algal biodiesel production is employed in this study as a potential addition to Uganda's renewable energy input because of Uganda's tropical climatic regime, sunshine, and wastewater. With three species of algae, i.e., Botryococcus braunii, Nannochloropsis sp., and Chlorella vulgaris, the research hypothesis is species compatibility, lipid extraction yield, and biodiesel quality in the Ugandan context. The methods used included growth condition optimization, hexane extraction, ethanol, methanol, chloroform solvent lipid extraction, and physicochemical biodiesel characterization yield. Results indicated Chlorella vulgaris to be the best species for decentralized systems since it recorded the maximum growth rate (13.4 cm biomass Day 12) and mid-level lipid yield (20–30%). Diethyl ether-isopropanol did the best in yield of 83.1% but was not safe, whereas hexane-isopropanol was the best compromise between viability and effectiveness. Biodiesel characteristics were conditionally met to ASTM requirements in that viscosity (2.82 mm²/s) and density (0.8335 g/cm³) were in compliance, but cetane values of 5.2 necessitated petrodiesel blending (B20). Algal biodiesel is techno-feasible in Uganda and enjoys the preference of low-cost open-pond systems, cooperative models at a community level, and integration of wastewater treatment to achieve energy poverty, environmental sustainability, and circular economy concepts.